2020
DOI: 10.1103/physrevmaterials.4.044801
|View full text |Cite
|
Sign up to set email alerts
|

In-plane ordering of oxygen vacancies in a high- Tc cuprate superconductor with compressed Cu-O octahedrons: An automated cluster expansion study

Abstract: A recently discovered high-Tc cuprate superconductor Ba2CuO4-δ exhibits exceptional Jahn-Teller distortion, wherein the CuO6 octahedrons are compressed along the c axis. As a consequence, the O vacancies prefer to reside in the CuO2 plane, but the exact structure is not known. By combining first-principles total energy calculation with the automated structure inversion method, the effective cluster interactions of O vacancies are mapped out. Around δ=0.8, where the 73K superconductivity was observed experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…2.4 Å in La 2 CuO 4 . A cluster expansion study [26] of compositions around δ ∼ 0.2 found that ordered supercells containing Cu-O P chains and ladders are favored up to 900 K. Our choices are guided by the chain structure of isovalent Sr 2 CuO 3 for δ=0, and by the simplest choices of added in-plane oxygen atoms (described below) for δ=1/4. These choices allow the assessment of differences due to coordination (there are four-, five-, and six-fold Cu ions), which seems to be a more useful viewpoint than crystal field splitting.…”
Section: A Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…2.4 Å in La 2 CuO 4 . A cluster expansion study [26] of compositions around δ ∼ 0.2 found that ordered supercells containing Cu-O P chains and ladders are favored up to 900 K. Our choices are guided by the chain structure of isovalent Sr 2 CuO 3 for δ=0, and by the simplest choices of added in-plane oxygen atoms (described below) for δ=1/4. These choices allow the assessment of differences due to coordination (there are four-, five-, and six-fold Cu ions), which seems to be a more useful viewpoint than crystal field splitting.…”
Section: A Methods Of Calculationmentioning
confidence: 99%
“…To describe models of ordered planar oxygens in the superconducting doped regime, we investigated three structures of doubled or quadrupled supercells (as necessary) having two or three Cu sites, with the z = c/2 layers pictured in Fig. 2 [18,25,26]. All structures are derived from the Ba 2 CuO 3 layers of Cu-O P chains in which each Cu has an apical O above and below.…”
Section: A Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are all in strong contradiction with the high-T c condition for the conventional cuprates, which suggests that an alternative pairing mechanism may be at work in this new material. Indeed, a number of theoretical studies have proposed various pairing mechanisms based on various lattice structures [9][10][11][12][13][14]. The experimental finding of Ba 2 CuO 3+δ may also shed a light on the previous finding of Sr 2 CuO 3+δ [15][16][17], which also possesses a large amount of oxygen deficiencies and a T c as high as 90 K but a much lower superconducting fraction than in the Ba 2 CuO 3+δ .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al propose a chain-type structure, which actually exists in Sr 2 CuO 3 [10,[18][19][20]. Li et al predict a ladder-type lattice based on an automated structure inversion method [12]. Le et al propose a structure where a matrix of Ba 2 CuO 4 with CuO 2 planes is embedded in the background of Ba 2 CuO 3 [11].…”
Section: Introductionmentioning
confidence: 99%